DEVELOPMENT OF ECOLOGY TEXTBOOK FOR SCIENCE EDUCATION STUDENTS - Indra Fardhani; Yayuk Mulyati; Erti Hamimi; Dewi Khajar Fitriana; Dewi Fitria Cahyani (Prodi Pendidikan IPA FMIPA Universitas Negeri Malang, 2021)
Ecology is one of the subjects that must be taken by undergrduate students. Lecture activities can certainly be hampered if there are no supporting textbooks. The purpose of this research is to provide textbooks that are in accordance with the demands of the curriculum by considering aspects of student needs, according to the characteristics and environment of students, helping students obtain alternative textbooks, and making it easier for educators in the learning process. This research method is Research & Development (R&D). In this study using the ADDIE’s development research model, it’s an appoarch that emphasizes an analysis of how each component interacts with each other by coordinating accordingly to the existing phases. Data collection techniques was using validation questionnaires for experts, individual test and small-scale trials. Data analysis results show that from material experts was 89.0% with the assessment criteria is very feasible, while the validation results by linguists was 71.4% with the assessment criteria is feasible. Readability tests shown percentage of 85.6% with the assessment criteria is very feasible. The product has an advantages and disadvantages which still needed to be revised.